Transforming English Correspondence Learning Through Flipped Classroom-Based Materials - Rr Sri Kartikowati; Dewi Nurmalasari; Eka Dewi Utari; Ria Rahma Nida; Ferry Setyadi Atmadja; Bayu Suhendry; Mayang Riyantie (Nurul Jadid University, 2026)
This study aimed to develop flipped classroom-based teaching materials for the English Correspondence course to improve students’ comprehension of professional written communication. The research was motivated by the limitations of conventional lecture-centered instruction, which often restricts student engagement and provides insufficient opportunities for independent and practice-oriented learning. A research and Development (R&D) approach employing the 4D model (Define, Design, Develop, Disseminate) was applied to systematically design, validate, and evaluate the instructional product. Data were collected through needs analysis, expert validation, student response questionnaires, and effectiveness testing using a pretest–posttest design. Expert validation results indicated a validity level of 86%, categorized as very valid, while practicality testing showed an 84% score, demonstrating that the materials were accessible and supportive of independent learning. Effectiveness testing revealed a significant improvement in students’ performance, with mean scores increasing from 58.51 (pretest) to 80.54 (posttest) and an N-gain value of 0.54, indicating moderate learning improvement. These findings suggest that flipped classroom-based teaching materials effectively enhance students’ conceptual understanding and practical competence in English business correspondence. The study implies that integrating validated digital instructional materials with student-centered learning models can strengthen technology-supported pedagogy and provide a scalable framework for improving professional communication learning in higher education.